A party system in flux: the Swedish parliamentary election of September 2018. Issue 7 (10th November 2019) - Aylott, Nicholas; Bolin, Niklas
Abstract: In the Swedish parliamentary election of 7 September 2018, the biggest parties, the Social Democrats and the Moderates, both lost votes compared to their scores in the previous election, but not as many as they had feared. Commensurately, the radical-right challenger party, the Sweden Democrats (SD), which had seemed certain to profit from Sweden's dramatic experience of the European migration crisis, did well, but not as well as it had hoped. The result left the array of parliamentary forces fragmented and finely balanced. Only after months of negotiations could a government be formed. Eventually, the incumbent coalition received a renewed parliamentary mandate. At the same time, the party system was transformed.